2018
DOI: 10.2166/wst.2018.322
|View full text |Cite
|
Sign up to set email alerts
|

Upflow packed bed Anammox reactor used in two-stage deammonification of sludge digester effluent

Abstract: The sludge digester effluent taken from a full scale municipal wastewater treatment plant (WWTP) in Istanbul, Turkey, was successfully deammonified using a laboratory scale two-stage partial nitritation (PN)/Anammox (A) process and a maximum nitrogen removal rate of 1.02 kg N/m3/d was achieved. In the PN reactor, 56.8 ± 4% of the influent NH4-N was oxidized to NO2-N and the effluent nitrate concentration was kept below 1 mg/L with 0.5–0.7 mg/L of dissolved oxygen and pH of 7.12 ± 12 at 24 ± 4°C. The effluent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Numerous studies reported that the start‐up of the anammox process in a bioreactor is usually time‐consuming and may take from months to years due to the low growth rates of anammox bacteria (the average doubling time is 11 days) . It also requires suitable environmental conditions of low dissolved oxygen (DO) concentration, with temperature and pH intervals of 30–40 °C and 7–8, respectively …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies reported that the start‐up of the anammox process in a bioreactor is usually time‐consuming and may take from months to years due to the low growth rates of anammox bacteria (the average doubling time is 11 days) . It also requires suitable environmental conditions of low dissolved oxygen (DO) concentration, with temperature and pH intervals of 30–40 °C and 7–8, respectively …”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have reported rapid and successful enrichment and operational strategies and factors influencing the anammox enrichment process. Examples include using different seeding sludge as inoculum, reactor type, medium carrier, and optimal operational conditions, determining the effect of various parameters, as hydraulic retention time, feeding load, DO, temperature . İbrahim et al., Çelen‐Erdem at al., Egli et al., and Uyanik et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations